2011
DOI: 10.1007/s10290-011-0114-x
|View full text |Cite
|
Sign up to set email alerts
|

Globalization drives strategic product switching

Abstract: Using firm-level panel data for Estonia, we analyse the impact of international competition on firm dynamics, considering both firm closedown and product switches. We contribute to the literature in two important ways: first, this is the first paper to study the determinants of exit and product switching in an emerging market; and second, we consider explicitly the role of export opportunities. Our results indicate that globalization does not affect firm exit significantly but it is an important factor explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Miranda et al (2012) andAmador and Opromolla (2013) are examples of papers investigating various dynamic aspects of FCP relations with European data (Estonia and Portugal, respectively), but do no present hazard rate analyses. 2 Examples areBesedeš and Prusa (2006a) andNitsch (2009).…”
mentioning
confidence: 98%
“…Miranda et al (2012) andAmador and Opromolla (2013) are examples of papers investigating various dynamic aspects of FCP relations with European data (Estonia and Portugal, respectively), but do no present hazard rate analyses. 2 Examples areBesedeš and Prusa (2006a) andNitsch (2009).…”
mentioning
confidence: 98%
“…Likewise, Rahu (2015) found that a number of determinants reduce the odds of product withdrawal from export markets, including product differentiation, product export share upon foreign entry, firm productivity, firm size, or foreign ownership. In a similar vein, Miranda et al (2012) found that external factors related to international competition are not significant for product exits, whose likelihood is negatively affected by firm age, productivity, as well as capital intensity.…”
Section: Resultsmentioning
confidence: 84%
“…In Ethiopia, MSEs occupy the lion's share of private-sector employment: an estimated 88%. In the manufacturing sector, MSEs have created job opportunities for about 1.1 million youth and women, reducing the national unemployment rate from 18% in fiscal year 2010-2011to 17.5% in FY 2011-2012(Esubalew & Raghurama, 2017. 2 As in other developing countries, Ethiopia could benefit hugely from the development of MSEs, the significance of which becomes clearer in light of the country's employment profile.…”
Section: Definition and Contextmentioning
confidence: 99%